The Mediating Effect of Intellectual Capital on Corporate Governance and Performance of Conglomerates in Nigeria - Ahmed Jinjri Bala; Anand Shankar Raja; Kabiru Isa Dandago (SEISENSE Journal of Management, 2019)
Purpose: The nature of diversification in the form of conglomerates is the research theme for this study. Thus, CG’s functions on FP on conglomerates firms of Nigerian economy was studied while applying IC as the mediating variable. Design/Methodology: This research depends on archival data collected from the NSE. Firms have been chosen based on the convenient sampling method and an important parameter for judgment is Conglomerated firms. In order to get genuine results, ten years of financial data have been taken into consideration. Multiple regression technique was used to analyze the data. The software used for analysis was STATA version 14.0. Results: The model I of the study disclose a pessimistic and insignificant impact of board size and board independence on IC using VAIC as a proxy. In contrast, model II results disclosed that the performance of the firms was impacted by the board’s size and institutional ownership. Implying that, the greater the size of the firm as well as more shares owned by institutional shareholders the higher the profit. Practical Implications: Nigeria being one of the growing economies now is dependent on knowledge assets and hence it has a positive effect on the firm’s performance. Conglomeration is seen even between employee’s skills of both industries, which give a positive outcome. Hence, firms under conglomerate tags have a strong impact in relation to intellectual capital.